Sec-O-Glucosylhamaudol Inhibits RANKL-Induced Osteoclastogenesis by Repressing 5-LO and AKT/GSK3β Signaling - Cao, Jinjin; Zhou, Ming-Xue; Chen, Xinyan; Sun, Menglu; Wei, Congmin; Peng, Qisheng; Cheng, Zhou; Sun, Wanchun; Wang, Hongbing (Frontiers in Immunology, 2022)
Sec-O-glucosylhamaudol (SOG), an active flavonoid compound derived from the root of Saposhnikovia divaricata (Turcz. ex Ledeb.) Schischk., exhibits analgesic, anti-inflammatory, and high 5-lipoxygenase (5-LO) inhibitory effects. However, its effect on osteoclastogenesis was unclear. We demonstrated that SOG markedly attenuated RANKL-induced osteoclast formation, F-actin ring formation, and bone resorption by reducing the induction of key transcription factors NFATc1, c-Fos, and their target genes such as TRAP, CTSK, and DC-STAMP during osteoclastogenesis. Western blotting showed that SOG significantly inhibited the phosphorylation of AKT and GSK3β at the middle–late stage of osteoclastogenesis without altering calcineurin catalytic subunit protein phosphatase-2β-Aα expression. Moreover, GSK3β inhibitor SB415286 partially reversed SOG-induced inhibition of osteoclastogenesis, suggesting that SOG inhibits RANKL-induced osteoclastogenesis by activating GSK3β, at least in part. 5-LO gene silencing by small interfering RNA in mouse bone marrow macrophages markedly reduced RANKL-induced osteoclastogenesis by inhibiting NFATc1. However, it did not affect the phosphorylation of AKT or GSK3β, indicating that SOG exerts its inhibitory effects on osteoclastogenesis by suppressing both the independent 5-LO pathway and AKT-mediated GSK3β inactivation. In support of this, SOG significantly improved bone destruction in a lipopolysaccharide-induced mouse model of bone loss. Taken together, these results suggest a potential therapeutic effect for SOG on osteoclast-related bone lysis disease.